COPD smokers who switched to e-cigarettes: health outcomes at 5-year follow up - Ricardo Polosa; Jaymin B Morjaria; Umberto Prosperini; Barbara Busà; Alfio Pennisi; Mario Malerba; Marilena Maglia; Pasquale Caponnetto (SAGE Publishing, 2020)
Background and Aims: The long-term health effects of the use of electronic cigarettes (ECs) in patients with chronic obstructive pulmonary disease (COPD) are largely unexplored. We present findings from a 5-year prospective assessment of respiratory parameters in a cohort of COPD patients who substantially reduced conventional smoking or achieved abstinence by switching to ECs. Methods: Patients were evaluated prospectively for their measurements of respiratory exacerbations, spirometric indices, quality of life using the COPD assessment tool (CAT), 6-min walk distance (6MWD), as well as conventional cigarette consumption. Baseline measurements prior to switching to EC use were compared with follow-up visits at 12-, 24-, 48- and 60-months. Age- and sex-matched COPD patients reporting to be regular smokers (not using ECs) were the reference group for the analysis. Results: Complete data were available from 39 patients. Those in the EC user group achieved a marked decline in cigarette smoking or abstinence. COPD EC users had a significant diminution in COPD exacerbations; with the mean (±SD) exacerbation rate falling from 2.3 (±0.9) at baseline to 1.1 (±1.0) at 5 years ( p  < 0.001), whereas no significant changes were observed in the control group. Significant and constant improvements in lung function, CAT scores and 6MWD were reported in the EC user group over the 5-year observation period compared with the reference group ( p  < 0.05). Conclusion: The present study suggests that EC use may ameliorate objective and subjective COPD outcomes, and that the benefits gained appear to persist long term. EC use for abstinence and smoking reduction may ameliorate some of the harm resulting from tobacco smoking in COPD patients.